Influence of surface acoustic waves on lateral forces in scanning force microscopies - Behme, G; Hesjedal, T (2001)
We present a detailed study of the influence of ultrasonic surface acoustic waves (SAWs) on point-contact friction. Lateral force microscopy (LFM) and multimode scanning acoustic force microscopy (SAFM) were used to measure and to distinguish between the influence of in-plane and vertical surface oscillation components on the cantilever's torsion and bending. The experiments show that friction can locally be suppressed by Rayleigh-type SAWs. Through the mapping of crossed standing wave fields, the wave amplitude dependence of the friction is visualized within microscopic areas without changing other experimental conditions. Above a certain wave amplitude threshold, friction vanishes completely. We found that the friction reduction effect is caused by the vertical oscillation components of the SAW. Purely in-plane polarized Love waves do not give rise to a significant friction reduction effect. Thus, we conclude that the mechanical diode effect, i.e., the effective shift of the cantilever off of the oscillating surface, is responsible for the SAW-induced lubrication. This explanation is supported by vertical and lateral SAFM measurements: in areas with completely vanishing friction, low frequency vertical cantilever oscillations are still observable, whereas lateral (torsional) cantilever oscillations are no longer excited. Additionally, at very high Rayleigh wave amplitudes an effect of lateral force rectification was observed. It results in a scan direction-independent appearance of the LFM traces. © 2001 American Institute of Physics.